2019
DOI: 10.1515/jafio-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Grain Storage and Losses in Ethiopia

Abstract: While storage losses at the farm are often assumed to be an important contributor to presumed large postharvest losses in developing countries, reliable and representative data on these losses are often lacking. We study farmers’ storage decisions and self-reported storage losses for grains based on two large-scale household surveys conducted in major agricultural areas in Ethiopia. We show that a relatively large share of grain production is stored by farm households for own consumption and that storage techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…Seeds and grains can be stored in a variety of structures under various storage conditions as food reserves, seeds for the next season, and to increase marketability [ 2 ]. Temperature, relative humidity, and seed moisture content are all important climatic factors for maintaining and preserving healthy seeds during storage [ 3 , 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds and grains can be stored in a variety of structures under various storage conditions as food reserves, seeds for the next season, and to increase marketability [ 2 ]. Temperature, relative humidity, and seed moisture content are all important climatic factors for maintaining and preserving healthy seeds during storage [ 3 , 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-harvest management of agricultural commodities is a significant challenge in developing countries, including Ethiopia [ 1 ]. In Ethiopia, 49% of grain crops, including oilseeds, are stored in traditional storage methods [ 2 ]. Dried commodities stored in such porous woven bags can gain moisture from environments with high relative humidity, allowing for fungal infections and the accumulation of mycotoxins [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was revealed that farmers in the different parts of Ethiopia has been using different traditional storage facilities (indoor or outdoor; gotera, gotta, keffo, barrels, and underground pits among others) to store their grain in different forms (Tadesse, 2008;Mohammed and Tadesse, 2018). Bachewe et al (2019) and Dubale (2014) also reported as different type of traditional storage structures were used to store different types of grains in various parts of Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…In rural areas, these "Chinese characteristics" are reflected in the entrepreneurial skills of Chinese farmer entrepreneurs, who can "collect" and use the huge and fragmented value of storage losses and fulfill their cash needs. Second, the government's support for the grain bank is crucial, especially during the financial crisis [47,48]. In the current system, one of the main responsibilities of the grain bank is to promote food security, so the sustainability of grain bank's operations depends on government support.…”
Section: Macro Conditions For Establishing a Grain Bankmentioning
confidence: 99%